The Application of Remarketing Techniques on Social Media to Increase Sales of PT Waysata Indonesia Bahagia - Dadang Dwi Sunjoko; Drs. Dr. Albari M.Si (International Journal of Education, Vocational and Social Science, 2024)
Advances in internet technology have had a significant influence on the transformation of contact and communication methods in the field of corporate marketing. This transition occurs from traditional face-to-face communication to digital communication, where interactions are carried out via screens. The purpose of this research is to determine remarketing techniques as a medium for making advertising more effective so that it can increase sales volume of PT. Waysata Indonesia Bahagia. This research uses qualitative methods, using two data collection techniques, namely observation and interviews. Remarketing is the right digital marketing strategy to give customers the opportunity to revisit previously visited websites to continue making purchases. PT. Waysata's remarketing work process is only broadcasting using WhatsApp media, carrying out paid advertising promotions on social media, not yet Segmenting the target market, so that untargeted advertising targets are still found by people who are not the company's target market. In making changes in the application of remarketing techniques. PT. Waysata Indonesia Bahagia carries out an STP strategy which then determines the target market from segmentation and then the company determines techniques or strategies for implementing remarketing. By using advertising with soft selling to avoid saturation of the target customers targeted by the company.